Question:

If one of the lines given by \( 6x^2 - xy + 4cy^2 = 0 \) is \( 3x + 4y = 0 \), then \( c \) equals

Show Hint

To solve problems like this, substitute the line equation into the given pair of straight lines equation and simplify the resulting expression.
Updated On: Jan 22, 2025
  • \( -3 \)
  • \( 1 \)
  • \( 3 \)
  • \( -1 \)
Hide Solution
collegedunia
Verified By Collegedunia

The Correct Option is A

Solution and Explanation

The given equation for the pair of straight lines is: \[ 6x^2 - xy + 4cy^2 = 0. \] One of the lines is \( 3x + 4y = 0 \). Substituting \( y = -\frac{3}{4}x \) into the equation: \[ 6x^2 - x\left(-\frac{3}{4}x\right) + 4c\left(-\frac{3}{4}x\right)^2 = 0. \] Simplifying the terms: \[ 6x^2 + \frac{3}{4}x^2 + 4c\left(\frac{9}{16}x^2\right) = 0, \] \[ 6 + \frac{3}{4} + \frac{36c}{16} = 0. \] Multiplying through by 16 to eliminate the fractions: \[ 96 + 12 + 36c = 0. \] Solving for \( c \): \[ 36c = -108 \quad \Rightarrow \quad c = -3. \] Final Answer: \[ \boxed{-3} \]
Was this answer helpful?
0
0